2016
DOI: 10.1007/s10143-016-0758-z
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic radiosurgery as a feasible treatment for intramedullary spinal arteriovenous malformations: a single-center observation

Abstract: Spinal cord intramedullary arteriovenous malformations are rare. For patients suffering from either hemorrhage or myelopathy, surgical or endovascular interventions are indicated. However, complete eradication of the nidus is often difficult because of its intramedullary location and complex angioarchitecture. In this report, we evaluate the feasibility and safety of stereotactic radiosurgery as a treatment modality for intramedullary spinal arteriovenous malformations (AVMs). Between 2010 and 2014, we perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…A recent article published in 2017 by Rashad and colleagues in Neurosurgical Review described a novel method for treating intramedullary AVMs using stereotactic radiosurgery [ 10 ]. Of note, this technique was used in two patients who had suffered haemorrhages and were not suitable for surgery or embolisation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent article published in 2017 by Rashad and colleagues in Neurosurgical Review described a novel method for treating intramedullary AVMs using stereotactic radiosurgery [ 10 ]. Of note, this technique was used in two patients who had suffered haemorrhages and were not suitable for surgery or embolisation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both complete and partial endovascular treatments have been shown to significantly decrease the risks of future hemorrhage [ 3 , 12 ]. SRS/SRT is another possible treatment option for intramedullary spinal AVM, though only a few series have been reported thus far [ 1 , 5 , 7 , 9 - 10 ]. The reported series are summarized in Table 2 .…”
Section: Discussionmentioning
confidence: 99%
“…He did not show any clinical improvement, probably because he had irreversible damage to the spinal cord. Rashad et al [ 1 ] reported the results in five cases, including one case of a spinal arteriovenous metameric syndrome. They used a lower radiation dose (biological equivalent dose (BED) = 72 Gy) and delivered 18 Gy in three fractions using the CyberKnife.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations